Buckwheat-enriched diet alleviates bisphenol A mediated oxidative stress via modulation of sirtuin 1 and antioxidant status in experimental rats. (30th March 2022) - Pande, Shubhra; Ranjan, Rajeev; Ryazanova, Maria; Shuvaev, Anton N.; Salmina, Alla B.; Kratasyuk, Valentina A.
Highlights: Dietary buckwheat countered bisphenol-A (BPA) induced oxidative stress in rats. Buckwheat enhanced sirtuin1 levels without affecting body weight. BPA did not affect sirtuin1 levels at given dose (10 mg L −1 ). Abstract: Present study investigated effect of dietary buckwheat in alleviating bisphenol A (BPA) mediated oxidative stress, concomitant sirtuin1 levels in serum, stomach, and liver of rats. Experimental group A and B ingested standard diet, C and D consumed buckwheat (30%); group A and C drank normal water, B and C had BPA contamination (10 mg L −1 ). Sirtuin1 mean B/A ratio nearing unity in all tissues reveals inertness of BPA towards sirtuin1. Dietary buckwheat improved sirtuin1 levels both in normal (mean C/A ratio of serum, 1.65; liver, 1.24; stomach, 1.78) and BPA fed state (mean D/B ratio of serum, 1.9; liver, 1.26; stomach, 1.75). Buckwheat augmented antioxidant status in BPA fed rats as seen in mean D/B ratio of serum (catalase, 2.4; glutathione reductase (GR), 1.33; Thiols, 1.2), liver (catalase, 2; GR, 2.5; Thiols, 1.36) and stomach (catalase, 1.31; GR, 1.5; Thiols, 1.33). Therefore, buckwheat counters BPA-led oxidative stress and modulates sirtuin1.